Thai Marriage Migrants in Germany and Their Employment Dilemma after the Residence Act of 2005 - Sinsuwan, Woramon (My University, 2017)
Thais started to migrate to Germany around the 1960s, and it is statistically evident that the feminisation of Thai migration through marriage to Germans has continued to the present day (Federal Statistics Office of Germany, 2016). Women account for almost 87 percent of all Thais in Germany. Marriages of Thai women to German or foreign husbands account for 94 percent of marriages in Germany involving Thai nationals, compared to only six percent of Thai men married to German or foreign wives. In 2005, the total number of Thais in Germany was 58,784; however, only 43 percent of Thais were registered as “labour” under the German employment system. This paper investigates the employment dilemma of Thai marriage migrants after implementation of the new Residence Act of 2005. First, it sheds light on the underlying problems that hinder Thai marriage migrants’ potential as full-time labourers and provides better understanding of why highly-educated Thai marriage migrants cannot fully integrate into the German labour market. Second, it examines the Thai diaspora and explores the present-day trans-nationalism of Thai marriage migrants in Germany. Finally, it applies Pierre Bourdieu’s theoretical concept of capital, habitus and social space to better understand Thai marriage migrants’ career choices in the German milieu. Qualitative interviews with 38 informants and a quantitative questionnaire filled out by 125 additional respondents were conducted between 2016 and 2017, providing one of the most comprehensive researches on Thai marriage migrants in Germany to date.

Seit ungefähr den 1960er Jahren migrieren Thailänder nach Deutschland, und es ist statistisch belegt, dass die Feminisierung der thailändischen Migration bis heute anhält (Bundesamt für Statistik, 2016). Frauen machen 87 Prozent aller in Deutschland lebenden Thailänder und Thailänderinnen aus. 94 Prozent aller Ehen mit thailändischer Beteiligung in Deutschland bestehen zwischen thailändischen Frauen und deutschen oder ausländischen Männern, während in nur 6 Prozent der Fälle thailändische Männer mit deutschen oder ausländischen Frauen verheiratet sind. Im Jahr 2005 waren 58.784 thailändische Staatsangehörige in Deutschland gemeldet, aber nur 43 Prozent davon waren nach dem deutschen Gesetz als „erwerbstätig“ registriert. Die vorliegende Arbeit untersucht das Beschäftigungsdilemma thailändischer Heiratsmigranten seit dem Inkrafttreten des neuen Aufenthaltsgesetzes im Jahr 2005. Zunächst beleuchtet sie die zugrundeliegenden Probleme, wegen derer die thailändische Heiratsmigranten ihr Potential als Vollzeit-Arbeitskräfte nicht ausschöpfen können, und erklärt, warum sich hochqualifizierte thailändische Heiratsmigranten nicht voll in den deutschen Arbeitsmarkt integrieren können. Dann untersucht sie die thailändische Diaspora und den Transnationalismus thailändischer Heiratsmigranten in Deutschland, und schließlich versucht sie, anhand Pierre Bourdieus Theorie von Kapital, Habitus und sozialem Raum die Berufsentscheidungen thailändischer Heiratsmigranten im deutschen Umfeld zu erklären. Qualitative Interviews, welche zwischen 2016 und 2017 durchgeführt worden sind, stellen mit 38 Informanten und einem quantitativen Fragebogen, der von 125 Befragten ausgefüllt wurde, bislang eine der umfangreichsten Forschungen über thailändische Ehemigranten in Deutschland dar.
Keywords: Ehe; Migration; Arbeitsmarkt; Erwerbstätigkeit; Diaspora; 331 Arbeitsökonomie; Heiratsmigration; Transnationalismus; sozialer Raum; Deutschland; Thailand